2018
DOI: 10.3389/fpsyg.2018.00309
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in Rule- vs. Plan-Based Movements Is Modulated by Action-Mode

Abstract: The rule/plan motor cognition (RPMC) paradigm elicits visually indistinguishable motor outputs, resulting from either plan- or rule-based action-selection, using a combination of essentially interchangeable stimuli. Previous implementations of the RPMC paradigm have used pantomimed movements to compare plan- vs. rule-based action-selection. In the present work we attempt to determine the generalizability of previous RPMC findings to real object interaction by use of a grasp-to-rotate task. In the plan task, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Differences in t 0 between approaches to action selection show that processes not directly involved in the decision differ. In our previous study with healthy young adults, we found significantly higher drift rates (v parameter) in the rule-task than in the plan-task, suggesting, that decision-relevant information processing can be more efficient in the rule-task than in the plantask (Scheib et al, 2018). The DDM is of particular value in the context of aging, as diffusion parameters have previously been shown to be sensitive to aging in a variety of cognitive tasks such as lexical-decision tasks (Ratcliff et al, 2004b), signal detection tasks (Ratcliff et al, 2001), letter discrimination tasks (Thapar et al, 2003), memory (Spaniol et al, 2006), and rapid two-choice decisions in general (Ratcliff et al, 2006(Ratcliff et al, , 2007.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Differences in t 0 between approaches to action selection show that processes not directly involved in the decision differ. In our previous study with healthy young adults, we found significantly higher drift rates (v parameter) in the rule-task than in the plan-task, suggesting, that decision-relevant information processing can be more efficient in the rule-task than in the plantask (Scheib et al, 2018). The DDM is of particular value in the context of aging, as diffusion parameters have previously been shown to be sensitive to aging in a variety of cognitive tasks such as lexical-decision tasks (Ratcliff et al, 2004b), signal detection tasks (Ratcliff et al, 2001), letter discrimination tasks (Thapar et al, 2003), memory (Spaniol et al, 2006), and rapid two-choice decisions in general (Ratcliff et al, 2006(Ratcliff et al, , 2007.…”
Section: Introductionmentioning
confidence: 66%
“…If-then rules (in some contexts referred to as Implementation Intentions) have been shown to facilitate many cognitive tasks (Gollwitzer and Sheeran, 2006;Wieber et al, 2015). Several motor cognitive studies have demonstrated that using such rules leads to shorter action initiation latency and reduced error rates compared to using a prospective planning approach when producing the same actions (Randerath et al, 2013(Randerath et al, , 2015(Randerath et al, , 2017Scheib et al, 2018;Stoll et al, 2022b). It has been hypothesized that rule-based action selection may have the potential to be particularly effective in improving the successful selection of grips in persons with difficulties in prospective planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the effectiveness of goals and plans may depend on where they draw athletes’ attention to. Some findings from research on plans generally support this assumption, albeit suggesting that plans can be more effective than action goals if they have an internal focus on performing the action [44], which seems to be the case in the field of motor actions as well [45]. The existing literature thus points to potentially complex interactions between the content of goals and plans and their effectiveness in the context of sport.…”
Section: Discussionmentioning
confidence: 99%
“…Pantomime of tool use is considered as very sensitive in detecting the presence of limb apraxia; typically the pantomime mode appears more sensitive as compared to actual tool use mode (3,15), however performance measures across these modes correlate and individual patterns appear stable (16,17). While both modes may retrieve similar concepts, differences may be represented by missing visuotactile feedback, i.e., the absence of mechanical interaction and cues from real objects, the heightened demand on imagery and the translation from mental images to motor execution (5,10,11,16,18,19). Contextual information may provide critical cues facilitating the access to an adequate motor concept and may constrain the possibilities for action production (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%